ANALISIS PENDAPATAN UNIVERSITAS INDONESIA - Vionita Yafi Nur Fadilah; Neysha Putri Lulytasari; Muhammad Munadi (STKIP Pesisir Selatan, 2026)
Objective: This study aims to examine the implementation of financial management in higher education institutions, focusing on the revenue management system at the University of Indonesia (UI). Referring to the Consolidated Financial Statements for 2021–2024, UI’s total revenue in 2024 amounted to IDR 3.66 trillion, increasing from IDR 3.40 trillion in 2023, representing a growth of IDR 260 billion or 7.65%. Operational revenue also rose from IDR 2.64 trillion to IDR 2.81 trillion, reflecting an increase of 6.44%. Meanwhile, UI’s endowment fund demonstrated consistent growth, rising from IDR 114.8 billion in 2021 to IDR 136.8 billion in 2024, equivalent to a total increase of 19.16% (an average of 6.4% annually). The endowment’s investment performance achieved an average annual return of 9.8%, exceeding the national inflation rate. These findings indicate that UI’s financial management has been carried out effectively through the application of accountability principles, revenue diversification, and transparent reporting. However, the contribution of non-academic revenue streams still requires enhancement to strengthen long-term financial independence. This study recommends fostering innovation in financial strategies, optimizing productive assets, and strengthening managerial capacity to support the institution’s financial sustainability.